The Impact of Long Class Duration on Attention Span: ELT Students’ Perceptions - Muyassaroh Muyassroh; Maulana Abdurrozikin; Muhammad Nashir (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2025)
This study aims at investigating the impacts of long class duration on attention span according to the students’ perception. In order to discover this research objective, qualitative method employed. Meanwhile, the data were collected through semi-structured interviews with ten English Language Teaching (ELT) students at Al-Qolam University who were selected using purposive sampling. The interviews were conducted in a mix of Indonesian and English to allow students to express their perceptions more freely. Then, the data were analysed thematically to identify recurring patterns and categories. Based on the interview, it can be confirmed that the respondents perceived that long class duration implemented at Al Qolam University gave negative impacts toward their attention span during the class activities. The negative impacts lied in students' fatigues both physically and mentally, focus fluctuation, and learning engagement within class activities. Key terms: long class duration, attention span, ELT